Qur’anic Interpretation of Freedom of Expression: Analysis of the Pesta Babi Film in Integration-Interconnection Paradigm - Siti Akhyu As'ari (Yayasan Insan Cendekia Nusantara, 2026)
Research Background: This article examines Qur’anic interpretation of freedom of expression through the case study of the film Pesta Babi and the controversy surrounding Mama Shinta, framed within the paradigm of integration-interconnection. The central issue addressed is how freedom of expression is negotiated between Qur’anic ethics and socio-cultural realities in Indonesia. Methods: The study employs a qualitative approach with a case study design. Data were collected through classical and contemporary Qur’anic exegesis, document analysis, and observation of public responses in media and digital platforms. Key Findings: The findings reveal that freedom of expression is not absolute but must be guided by Qur’anic ethics and the objectives of maqasid al-shariah. Public debates, including polarized reactions in digital spaces, demonstrate that uncontrolled expression can trigger cultural tensions and identity conflicts. Contribution: This article offers theoretical contributions by contextualizing Qur’anic exegesis within contemporary socio-cultural issues, and practical contributions by providing insights for society to balance freedom of expression with social harmony. The effort to present the Qur’an as an ethical reference highlights its relevance to current debates on freedom of expression in the digital era. Conclusion: Qur’anic interpretation can serve as an ethical framework for freedom of expression, enabling it to function as constructive social critique rather than a source of conflict.